Myocardial and Systemic Inflammation in Acute Stress-Induced (Takotsubo) Cardiomyopathy. Issue 13 (26th March 2019) - Scally, Caroline; Abbas, Hassan; Ahearn, Trevor; Srinivasan, Janaki; Mezincescu, Alice; Rudd, Amelia; Spath, Nicholas; Yucel-Finn, Alim; Yuecel, Raif; Oldroyd, Keith; Dospinescu, Ciprian; Horgan, Graham; et al.
Abstract : Background: Acute stress-induced (takotsubo) cardiomyopathy can result in a heart failure phenotype with a prognosis comparable with that of myocardial infarction. In this study, we hypothesized that inflammation is central to the pathophysiology and natural history of takotsubo cardiomyopathy. Methods: In a multicenter study, we prospectively recruited 55 patients with takotsubo cardiomyopathy and 51 age-, sex-, and comorbidity-matched control subjects. During the index event and at the 5-month follow-up, patients with takotsubo cardiomyopathy underwent multiparametric cardiac magnetic resonance imaging, including ultrasmall superparamagnetic particles of iron oxide (USPIO) enhancement for detection of inflammatory macrophages in the myocardium. Blood monocyte subpopulations and serum cytokines were assessed as measures of systemic inflammation. Matched control subjects underwent investigation at a single time point. Results: Subjects were predominantly middle-aged (64±14 years) women (90%). Compared with control subjects, patients with takotsubo cardiomyopathy had greater USPIO enhancement (expressed as the difference between pre-USPIO and post-USPIO T2*) in both ballooning (14.3±0.6 milliseconds versus 10.5±0.9 milliseconds; P <0.001) and nonballooning (12.9±0.6 milliseconds versus 10.5±0.9 milliseconds; P =0.02) left ventricular myocardial segments. Serum interleukin-6 (23.1±4.5 pg/mL versus 6.5±5.8 pg/mL; P <0.001) and chemokine (C-X-C motif) ligand 1 (1903±168 pg/mL versus 1272±177 pg/mL; P =0.01) concentrations and classic CD14 ++ CD16 - monocytes (90±0.5% versus 87±0.9%; P =0.01) were also increased whereas intermediate CD14 ++ CD16 + (5.4±0.3% versus 6.9±0.6%; P =0.01) and nonclassic CD14 + CD16 ++ (2.7±0.3% versus 4.2±0.5%; P =0.006) monocytes were reduced in patients with takotsubo cardiomyopathy. At 5 months, USPIO enhancement was no longer detectable in the left ventricular myocardium, although persistent elevations in serum interleukin-6 concentrations ( P =0.009) and reductions in intermediate CD14 ++ CD16 + monocytes (5.6±0.4% versus 6.9±0.6%; P =0.01) remained. Conclusions: We demonstrate for the first time that takotsubo cardiomyopathy is characterized by a myocardial macrophage inflammatory infiltrate, changes in the distribution of monocyte subsets, and an increase in systemic proinflammatory cytokines. Many of these changes persisted for at least 5 months, suggesting a low-grade chronic inflammatory state. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02897739. Abstract : Supplemental Digital Content is available in the text.